Pseudoknots: RNA Structures with Diverse Functions - Staple, David W; Butcher, Samuel E (PLOS Biology, 2005)
Just as proteins form distinct structural motifs, certain structures are commonly adopted by RNA molecules. Amongst the most prevalent is the RNA pseudoknot.